Rapid treatment of full‐thickness skin loss using ovine tendon collagen typeIscaffold with skin cells - Mh Busra Fauzi; Nor Fadilah Rajab; Yasuhiko Tabata; Aminuddin Bin Saim; Ruszymah Bt Hj Idrus; Shiplu Roy Chowdhury (2019)
The full-thickness skin wound is a common skin complication affecting millions of people worldwide. Delayed treatment of this condition causes the loss of skin function and integrity that could lead to the development of chronic wounds or even death. This study was aimed to develop a rapid wound treatment modality using ovine tendon collagen type I (OTC-I) bio-scaffold with or without noncultured skin cells. Genipin (GNP) and carbodiimide (EDC) were used to cross-link OTC-I scaffold to improve the mechanical strength of the bio-scaffold. The physicochemical, biomechanical, biodegradation, biocompatibility, and immunogenicity properties of OTC-I scaffolds were investigated. The efficacy of this treatment approach was evaluated in an in vivo skin wound model. The results demonstrated that GNP cross-linked OTC-I scaffold (OTC-I_GNP) had better physicochemical and mechanical properties compared with EDC cross-linked OTC-I scaffold (OTC-I_EDC) and noncross-link OTC-I scaffold (OTC-I_NC). OTC-I_GNP and OTC-I_NC demonstrated no toxic effect on cells as it promoted higher cell attachment and proliferation of both primary human epidermal keratinocytes and human dermal fibroblasts compared with OTC-I_EDC. Both OTC-I_GNP and OTC-I_NC exhibited spontaneous formation of bilayer structure in vitro. Immunogenic evaluation of OTC-I scaffolds, in vitro and in vivo, revealed no sign of immune response. Finally, implantation of OTC-I_NC and OTC-I_GNP scaffolds with noncultured skin cells demonstrated enhanced healing with superior skin maturity and microstructure features, resembling native skin in contrast to other treatment (without noncultured skin cells) and control group. The findings of this study, therefore, suggested that both OTC-I scaffolds with noncultured skin cells could be promising for the rapid treatment of full-thickness skin wound.